Financial Ratio Analysis and Evaluation to Measure the Financial Health and Condition of the Company. Case Study of: Five Subsidiary Companies of PT. Saratoga Ivestama Sedaya Tbk. for the periods of 2013-2015 - Hendrita, Sarah; Daryanti, Wiwiek M. (The Indonesian Journal of Business Administration, 2017)
Abstract. PT. Saratoga Investama Sedaya Tbk as one of the investment companies in Indonesia and has many subsidiaries. The company focuses on investing in three business sectors, namely natural resources, infrastructure, and consumers. Assessment related to investment opportunity, become more important for the company. The assessment can be seen from several aspects, one of which is the assessment of the financial aspects of the company. The objective of the study is to carry out an assessment of financial aspect whether financially the subsidiary is classified in a very healthy company, healthy, and unhealthy respectively. The method used in this study is Financial Ratio Analysis, which is classified into four categories: 1. Profitability; 2. Liquidity; 3. Solvency; and 4. Activity Ratios. The results of this study will be validated by using: 1. the Decree of the Minister of State Owned Enterprises no. KEP-100 / MBU / 2002 on the health assessment of State-Owned Enterprises and 2. The Weighted Average Cost of Capital (WACC) of each subsidiary. The data used in this study is derived from the audited financial statements of each subsidiary:  ADRO, MPMX, NRCA,TBIG, and PALM during the last three years of the periods 2013 – 2015. The results of this study indicate that during the periods it show ADRO, MPMX, NRCA, and TBIG are categorized as very healthy companies and PALM is categorized as a healthy company.Keywords: Financial Ratios, Weighted Average Cost of Capital, Cost of Debt, ost of Equity, Decree of the Minister of SOEs No. KEP-100/MBU/2002